Design conversion, and performance estimation of BLDC motor in hybrid electric vehicle - Ganesan, Thenmozhi; Vanaraj, Chandra; Subramanian, Manoharan; Alagesan, Radhika (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The core concept in this paper is to hybridize a conventional engine-powered two-wheeler into a hybrid electric vehicle. The shift in the consumers’ mindset from conventional IC engine vehicles to electric/hybrid vehicles may be a challenge due to the high initial investment. Hence, as a preliminary work, it is proposed to convert an IC engine vehicle to a hybrid electric vehicle considering factors such as affordability, user control, and flexibility. To make the hybrid vehicle available at an affordable price, lead-acid batteries are used for the study. Also, the BLDC motor used in this vehicle was designed and developed according to the available design constraints. The moped was redesigned to operate in either engine or electric mode individually depending on the rider’s desire and can switch over to any mode at any time as intended. This is achieved using a unique switching mechanism constructed using needle roller bearings. The concept of hybridization thus results in reduced emissions, especially in stop-go traffic where electric mode can be used, and the performance of hybrid electric vehicles is estimated.